(untitled) (FULafia Journal of Science and Technology, 2023)
This study was conducted to evaluate the effects of utilization of Bone meal, Limestone, Oyster shell and Egg shell as Calcium and Phosphorous mineral sources on performance, carcass and bones characteristics of broilers. A total of sixty (60) four (4) weeks old broiler chicks were raised on commercial chick mash (1- 30 d) prior to the commencement of the experiment and experimental diets were formulated to provide approximately 3050-3100 kcal/ME, 19-20% crude protein (CP) using the least cost feed formulation software feed win during the 21 d feeding trial period. The experimental birds were assigned to four (4) dietary treatments groups of two (2) replicates in a completely randomized design with 2.5 % inclusion of limestone), oyster shell, bone meal) and egg shell constituting the treatments. Significant (P<0.05) differences were observed in some performance parameters like feed intake (FI), weight gain (WG) and feed conversion ratio (FCR). Similarly some carcass parameters were also significantly affected by the experimental treatments. The effects on bone characteristics were significant (P<0.05). There was no consistent trend in the differences observed for all test Ca and P sources. It is therefore recommended that all the experimental calcium sources can be included to constitute up to 2.5% in the diet of broiler chicken. This will afford small scale poultry producers the control of using eggshell, bone meal, limestone and oyster shell as sources of calcium, phosphorus and other minerals for sustainable broiler chicken production